Durable Sustained Virologic Response After Oral Directly Acting Antiviral Therapy Despite Immunosuppressive Treatment. (31st July 2015) - Hahn, Katherine J.; Kohli, Anita; Sims, Zayani; Kottilil, Shyamasundaran
Abstract: Treatment for hepatitis C has evolved from interferon-based therapy to all oral, directly acting antiviral (DAA) therapy. The influence of immunosuppression on maintaining sustained virologic response (SVR) in patients who have been treated with these directly acting agents is unknown. In this study, we report sustained hepatitis C virus (HCV) suppression in 3 patients undergoing various immunosuppressive treatments after achieving SVR with DAA therapy. Three patients, who were enrolled in 1 of 2 single-center National Institutes of Health clinical trials, achieved SVR12. Each patient had undergone between 6 and 24 weeks of DAA therapy with or without ribavirin. Immunosuppression was varied among the 3 patients. Therapy included adalimumab, carboplatin/irinotecan, or capecitabine. In all 3 cases, patients maintained HCV RNA levels below detection after immunosuppression. All patients had undetectable viral load and normalized liver-related enzymes during immunosuppressive therapy. This report suggests that SVR as a result of novel DAA therapy is durable and likely not affected by immunosuppressive therapy. Larger studies are required to confirm these results, but findings are promising for the treatment of large numbers of HCV-infected patients who may require subsequent immunosuppressive or immunomodulating therapies.